Alpha thalassaemia is associated with increased soluble transferrin receptor levels. - Rees, D; Williams, T; Maitland, K; Clegg, J; Weatherall, D (1998)
Although alpha+ thalassaemia is the commonest haemoglobinopathy in the world, it is not known if it is associated with significant ineffective erythropoiesis, a fact of importance in interpreting its complex interaction with malaria. To study this problem, we have measured the concentrations of soluble transferrin receptor (sTIR) and ferritin in 181 children from Vanuatu with heterozygous (68) and homozygous (46) alpha+ thalassaemia, and normal controls (67). sTfR concentrations were significantly higher in both homozygotes (mean 3.1 mg/l, range 2.8-3.4) and heterozygotes (2.86 mg/l, 2.6-3.2) compared to the normal controls (2.48 mg/l, 2.3-2.7), suggesting that although globin chain imbalance is minimal, there is ineffective erythropoiesis in both these conditions. Age was also shown to significantly affect sTfR, with peak levels occurring in the 5-9 years age group. Ferritin concentrations showed a similar trend, being higher in the thalassaemic groups, although this did not reach statistical significance. No individuals had low ferritin concentrations, although two had significantly elevated sTfR levels. These observations suggest that the alpha+ thalassaemia phenotype includes an expansion of the erythron, and may suggest possible mechanisms for the increased susceptibility in babies with alpha thalassaemia to both P. falciparum and P. vivax malaria.